POWER PRAXIS AT THE BEGINNING OF THE MEIJI ERA: TRADITION AND MODERN DISCOURSE - Cahyasari, Intannia; Efendi, Anwar (ATAVISME, 2018)
This study aims to investigate how the discourse of Japanese society tradition with conservative mindset as the impact of Tokugawa power that applied sakoku (isolation politics) for more than two hundred years began questioned, criticized and disputed in Hanauzumi?s novel by Jun'ichi Watanabe. This study uses Foucault's discourse approach that is applied to express the form of discourse by external and internal exclusion. This research uses a qualitative descriptive method, the data collected is data that explains the problem of production and distribution of discourse based on Foucault's external and internal exclusion. The results of this study indicate that Jun'ichi Watanabe produces, distributes and transforms modern discourse as counter discourse against the discourse of tradition to change the way of thinking, customs and culture that harm women.